Revised contraindications for the use of non-medical WB-electromyostimulation. Evidence-based German consensus recommendations - von Stengel, S.; Fröhlich, M.; Ludwig, O.; Eifler, C.; Berger, J.; Kleinöder, H.; Micke, F.; Wegener, B.; Zinner, C.; Mooren, F. C.; Teschler, M.; Filipovic, A.; et al. (Frontiers in Sports and Active Living, 2024)
Whole-body electromyostimulation has proven to be a highly effective alternative to conventional resistance-type exercise training. However, due to adverse effects in the past, very extensive contraindications have been put in place for the commercial, non-medical WB-EMS market. Considering recent positive innovations e.g., federal regulation, mandatory trainer education, revised guidelines, and new scientific studies on WB-EMS application, we believe that a careful revision of the very restrictive contraindications on WB-EMS is needed. This applies all the more because many cohorts with limited options for conventional exercise have so far been excluded. During a first meeting of an evidence-based consensus process, stakeholders from various backgrounds (e.g., research, education, application) set the priorities for revising the contraindications. We decided to focus on four categories of absolute contraindications: “Arteriosclerosis, arterial circulation disorders”, “Diabetes mellitus” (DM), “Tumor and cancer” (TC), “Neurologic diseases, neuronal disorders, epilepsy”. Based on scientific studies, quality criteria, safety aspects and benefit/risk assessment of the category, DM and TC were moved to the relative contraindication catalogue, while arteriosclerosis/arterial circulation disorders and neurologic diseases/neuronal disorders/epilepsy were still considered as absolute contraindications. While missing evidence suggests maintaining the status of neurologic diseases/neuronal disorders as an absolute contraindication, the risk/benefit-ratio does not support the application of WB-EMS in people with arteriosclerosis/arterial circulation diseases. Despite these very cautious modifications, countries with less restrictive structures for non-medical WB-EMS should consider our approach critically before implementing the present revisions. Considering further the largely increased amount of WB-EMS trials we advice regular updates of the present contraindication list.